Photon-photon and pomeron-pomeron processes in peripheral heavy ion collisions - Roldão, C. G. [UNESP]; Natale, A. A. [UNESP] (American Physical Society (APS), 2000)
We estimate the cross sections for the production of resonances, pion pairs, and a central cluster of hadrons in peripheral heavy-ion collisions through two-photon and double-pomeron exchange, at energies that will be available at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC). The effect of the impact parameter in the diffractive reactions is introduced, and by imposing the condition for realistic peripheral collisions we verify that in the case of very heavy ions the pomeron-pomeron contribution is indeed smaller than the electromagnetic one. However, they give a non-negligible background in the collision of light ions. This diffractive background will be more important at RHIC than at LHC.